Proteome-wide comparison of tertiary protein structures reveals molecular mimicry in Plasmodium-human interactions - Muthye, Viraj; Wasmuth, James D. (Frontiers in Parasitology, 2023)
Molecular mimicry is a strategy used by parasites to escape the host immune system and successfully transmit to a new host. To date, high-throughput examples of molecular mimicry have been limited to comparing protein sequences. However, with advances in the prediction of tertiary structural models, led by Deepmind’s AlphaFold, it is now possible to compare the tertiary structures of thousands of proteins from parasites and their hosts, to identify more subtle mimics. Here, we present the first proteome-level search for tertiary structure similarity between the proteins from Plasmodium falciparum and human. Of 206 P. falciparum proteins that have previously been proposed as mediators of Plasmodium-human interactions, we propose that seven evolved to molecularly mimic a human protein. By expanding the approach to all P. falciparum proteins, we identified a further 386 potential mimics, with 51 proteins corroborated by additional biological data. These findings demonstrate a valuable application of AlphaFold-derived tertiary structural models, and we discuss key considerations for its effective use in other host-parasite systems.